The Horseshoe Crab: A Poster - Florida Master Naturalist Program (EDIS, 2004)
Each year, many thousands of horseshoe crabs are stranded upside-down and die. Horseshoe crabs are gentle and WON'T bite or sting you. Turn them over by the edge of their shell. Don't flip them by their tail! Horseshoe crabs are important to the coastal ecosystem, and research derived from horseshoe crabs helps save human lives!